Physical activity and sedentary behaviour among children and adolescents with intellectual disabilities during the COVID‐19 lockdown in China. Issue 12 (3rd November 2021) - Yuan, Y. Q.; Ding, J. N.; Bi, N.; Wang, M. J.; Zhou, S. C.; Wang, X. L.; Zhang, S. H.; Liu, Y.; Roswal, G.
Abstract: Background: In the wake of the COVID‐19 pandemic, preliminary research has reported a significant decline in physical activity (PA) and an increase in sedentary behaviour (SB) among typically developed children and adolescents. Limited research has looked at the current situation of PA and SB during this pandemic among children and adolescents with intellectual disabilities (ID). This study investigated the situations about PA and SB among school‐aged children and adolescents with ID on China's mainland during the COVID‐19 outbreak. Methods: In total, 837 parents of children and adolescents (ages 6–18 years) with ID from 15 special education schools of Shandong Province in China were recruited through convenience sampling in the study. Parents reported PA and SB among children and adolescents with ID through the Children's Leisure Activities Study Survey‐Chinese version (CLASS‐C) online questionnaires. Results: From parents' reports, Chinese children and adolescents with ID during the COVID‐19 pandemic participated in approximately 10 min of moderate‐to‐vigorous physical activity, and engaged in approximately 530 min of SB every day. Meanwhile, only 17.4% of children and adolescents with ID were able to achieve the recommendation of 60 min of daily moderate‐to‐vigorous physical activity and 76.1% of children and adolescents with ID spent more than 2 h on SB per day. Additionally, the problems of decrease PA and excessive SB were more prominent in older adolescents with ID compared with younger children with ID. Conclusion: In China, the low level of PA and high level of SB is particularly evident in children and adolescents with ID during the outbreak of COVID‐19. The great majority of children and adolescents with ID did not meet the recommended amount of PA while undergoing excessive SB under the long‐term home quarantine environment. Therefore, immediate attention and great effort should be made to deal with this severe situation among this vulnerable population in the mainland of China.